Evaluation of physical activity levels and anthropometric measurements in Turkish adults - Karaca, Kezban Esen; Toprak, Dilek; Dogan, Nurhan; Ersoy, Nesli; Ersoy, Gülgün (Progress in Nutrition, 2021)
Background: The aim of this study is to determine the relationship between physical activity levels and antropometric measurements of Turkish adults.Materials and Method: The data were obtained via interviews with a questionnaire from 3453 subjects, who were chosen with simple random sampling among adults. Their anthropometric measurements were taken. Physical activities done in previous week were evaluated via International Physical Activity Questionnaire (IPAQ). The statistical analyses were made in SPSS 16.0 package program.Results: 47.5% (n=1639) of the participants were female and 52.5% (n=1814) were male.71.1 % (n=2476) of male subjects were high school and below graduates and 28.3% (n=977) of them were university and higher graduates. Vigorous, moderate and walking IPAQ total scores of all group were 3465.91 met-min/week, 960.66 met-min/week, 758.81 met-min/week respectively. %18.1 (n=626) of the participants were doing vigorous,%27.3 (n=944) of them were doing moderate physical activity and %90.6 (n=3127) of the participants were preferred walking.                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                   Conclusion: Gender, age, BMI (weight) and socioeconomic status have effects on physical activity level of Turkish adults.Keywords: physical activity, anthropometric measurements, BMI, body mass index